Teoria wartości Karola Marksa a problemy kształtowania cen w gospodarce socjalistycznej - Romanow, Zbigniew (Wydział Prawa i Administracji UAM, 1984)
Speaking on an ambivalent character of labor and consequently on the whole economic process, K. Marx emphasises that it is both the process of increasing values and generating utility value. He does not also treat a relation of theory of value to a price making process directly and onesidedly. Prices have to reflect verified effects of social labor expenditures and not only an ordinary acceptance of it under conditions of material-utility criteria of managing economy and in the competitive buyer-consummer market. A rational true price has to reflect real economic proportions resulting from a long term and perspective plan as well as currently formed economic conditions effected by the given productive machinery and market situation. The law of value cannot act as a law of prices in its classic formulation, under these conditions even in the increasing role of commodity- -monetary categories. Yet it can act as a law of labor expenditures determining possibilities of fulfilling needs of production and consumption within the framework of basic productive and exchange proportions included in a long term plan and in autonomous decisions of enterprises. Consequently, adopting a cost concept of prices in economic literature is not satisfactory from the point of view of realizing a natural target of production and socio-economic rationality. It seems that the concept of prices of market equilibrium is rather closer to rational principles of price making, handling price as an objective category reflecting real proportions and conditions of economy, under one condition though: it can not be treated as a result of unrestrained formation of economic processes.
The Marxian theory of value and problems of price making in socialist economy